Integrative and complementary practices, mental disorders and life satisfaction among university students (Research, Society and Development, 2021)
Objective: to identify the relationships between satisfaction with life, symptoms of anxiety and depression, and integrative and complementary practices in university students in the health area. Methodology: quantitative descriptive research with students from the Federal University of Sergipe. The collection period took place between the months of August 2018 and November 2019. Associations between categorical variables were performed using Pearson's chi-square test. Results: a significant association was found between anxiety symptoms and the period in which students are in the academic grade, lost module and main complaint. Depression symptoms were associated with age group, lost module and satisfaction with the course. Conclusion: There is conditional dependence and the relationship of satisfaction with life between age, course, satisfaction with the course and satisfaction with the method is influenced by the condition of attending or not the care room.